ANALISIS PREFERENSI KONSUMEN TERHADAP PRODUK PERAWATAN DIRI (SKINCARE) LOKAL YANG MEMPENGARUHI CUSTOMER LOYALTY - Arbi Siti Rabiah; Fransiska Anggriany Stefany (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study discusses the relationship between consumer preferences for local skin care products that affect consumer loyalty. The purpose of this study was to analyze the effect of Customer Preference on Customer Loyalty mediated by Price, Promotion, and Percieved Quality on local skincare. This study used 208 respondents with questionnaires distributed online through social media platforms. The selected respondents are Millennials, and Gen z who have or are currently using local skincare who are domiciled in Greater Jakarta. This research uses descriptive-quantitative with the help of SPSS version 20 data application. The results achieved in this study are that there is a significant influence between Customer Preference on Customer Loyalty mediated by Price, Promotion, and Perceived Quality as intervening variables.